The Effect of Interpersonal Communication and Self-Efficacy on Employee Performance with Procrastination as a Mediator Variable - Desi Sari; Utami Dewi Indriyati; Sintha Pitaloka; Zainun Mu’tadin (People and Behavior Analysis, 2026)
In today’s increasingly competitive work environment, employee performance plays a critical role in the success of any organization, especially in public services. However, poor communication and low self-confidence among employees, coupled with monotonous work routines, often lead to procrastination and reduced productivity. These issues not only affect individual performance but also the efficiency of public service delivery. This study aims to examine the influence of interpersonal communication and self-efficacy on employee performance, with procrastination serving as a mediator variable. The research was conducted with employees at the Land Office in City X, using a purposive sampling technique. The results showed that interpersonal communication had a positive path coefficient of 0.290 on employee performance, while self-efficacy had a stronger direct path coefficient of 0.668. The effect of both interpersonal communication and self-efficacy on employee performance through procrastination was weaker, with path coefficients of -0.121 and -0.059, respectively. This study highlights the importance of fostering effective communication and strengthening employees’ self-confidence to enhance performance, and offers valuable insights for improving managerial strategies in public-sector organizations.